Saving of heat energy costs while providing residents with heat and hot water - A.K. Khassenov; B.R. Nussupbekov; D.Zh. Karabekova; M. Stoev; B.K. Zeinolla; A.K. Muratova (Қарағанды университетінің хабаршысы. Физика сериясы)
In the article data on the amount of heat while providing consumers with heat and hot water are presented. The installation of heat meters is necessary to improve the standard of living of the population through the efficient use of heat energy. Various devices are used to take account of the consumption of heat in heat supply and hot water supply to consumers. Heat metering devices have been started to be installed in residential buildings in recent years. Questions connected to account of heat consumption and its cost is very important these days. The considered commercial heat metering station includes a heat meter, a mass meter or a heat carrier volume, pressure and temperature sensors. We only need to calculate the meter to save energy for heat energy because we only have to pay for the heat we consume. While equipping a residential house with heat metering devices, it was observed that payment for heat energy and consumed hot water was beneficial for consumers.